2022
DOI: 10.1155/2022/9506227
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis HG‐15, a Halotolerant Rhizoplane Bacterium, Promotes Growth and Salinity Tolerance in Wheat (Triticum aestivum)

Abstract: Certain plant growth-promoting bacteria (PGPB) reduce salt stress damage in plants. Bacillus subtilis HG-15 is a halotolerant bacterium (able to withstand NaCl concentrations as high as 30%) isolated from the wheat rhizoplane in the Yellow River delta. A qualitative and quantitative investigation of the plant growth-promoting characteristics of this strain confirmed nitrogen fixation, potassium dissolution, ammonia, plant hormone, ACC deaminase, and proline production abilities. B. subtilis HG-15 colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Moreover, Lastochkina et al [ 49 ] reported that B. subtilis inoculation in response to salinity stress and Pro accumulation was reduced in Phaseolus vulgaris under salinity. Similar retardation of Pro content was also found with the endophytic inoculation of B. subtilis in the salt-affected Triticum aestivum plants [ 50 ]. Moreover, microbes accelerated the production of EPS which enhanced adherence of soil particles and also aided in promoting macropore production to improve the soil porosity and aeration under stressful environments, thus maintaining osmotic adjustment [ 51 ].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, Lastochkina et al [ 49 ] reported that B. subtilis inoculation in response to salinity stress and Pro accumulation was reduced in Phaseolus vulgaris under salinity. Similar retardation of Pro content was also found with the endophytic inoculation of B. subtilis in the salt-affected Triticum aestivum plants [ 50 ]. Moreover, microbes accelerated the production of EPS which enhanced adherence of soil particles and also aided in promoting macropore production to improve the soil porosity and aeration under stressful environments, thus maintaining osmotic adjustment [ 51 ].…”
Section: Discussionsupporting
confidence: 73%
“…These biofilms can regulate nutrient and water consumption from the rhizosphere, performing as a strong osmo-regulating tool under stress [ 56 ]. Ji et al [ 18 ] demonstrated that Bacillus inoculation in salt affected T. aestivum seedlings mitigated cellular dehydration through regulating the osmolytes accumulation, such as Pro and soluble sugars. Similarly, by inoculating Bacillus in the salt stressed T. aestivum [ 57 ], the salt-induced osmotic stress was mitigated by lowering the Pro synthesis, which is in congruence with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among the PGPRs, Bacillus is one of the promising genera as it helps to improve plant growth and physiology and encourages plant survivability under stress conditions. An inoculation of Bacillus helps to enhance the plant growth and water holding capacity and minimizes the Na + toxicity, lipid peroxidation, ethylene formation, and electrical conductivity, subsequently mitigating salt-induced injuries [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microbial inoculant is a compound agent of Bacillus subtilis HG-15 and Bacillus velezensis JC-K3. Both strains exhibit efficient antagonistic activity and other growth-promoting characteristics, as described in our previous studies (Ji et al, 2021;Ji et al, 2022). Luria-Bertani liquid medium was used as a seed and fermentation medium.…”
Section: Biocontrol Strain and Culture Mediummentioning
confidence: 96%
“…Bacillus subtilis HG-15 and Bacillus velezensis JC-K3, the strains used in this study, are salt-tolerant bacteria obtained, respectively, from the rhizoplane and inside the roots of wheat in the saline soil of Yellow River Delta; the strains did not inhibit each other and were able to colonize stably in the inter-root of saline wheat, both with the properties of producing ACC deaminase, IAA, Siderophore, and proline. The strains have been demonstrated to promote wheat seedling growth, reduce salt stress damage, and improve photosynthesis and osmoregulation in pot experiments ( Ji et al., 2021 ; Ji et al., 2022 ). More studies have shown that combined bacterial inoculum has higher environmental adaptability, biological viability, and synergistic metabolism levels than single strains and has a greater impact on soil-plant material cycling ( Dombrowski et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%